Three case studies of landscape design project of Italian marginal areas. An anti-fragile opportunity for an integrated food governance in a post Covid perspective. (April 2023) - Dezio, Catherine; Paris, Mario
Abstract: The recent pandemic has brought marginal territories back to the center of political and academic debates, providing an opportunity to restart territorial projects. Agro-ecosystems and their derivations (Urban gardens, local supply chains, ecosystem services, typical products, rural tourism), which involve very different areas of the territory, could act as activators for a resilient development model for fragile contexts. However, this implies connected and integrated policy and planning tools, envisioning sustainable management methods for production, and integrating them with chains and tourism economy in dialogue with a landscape design vision. Therefore, this paper is aimed to test the urban design project as a tool to integrate interventions, which especially in the rural context are characterized by overlapping objectives. An experimental attempt will be made on three landscape design projects in marginal rural areas with the integration of tangible and intangible actions and a view of a sustainable and resilient restart. The projects analyzed are not so often used as much as static best practices, but in applying the consolidated research-by-design approach. Through it, we suggested four directions to understand and intervene in co-evolutionary processes through mechanisms of composition and decomposition from the urban planning/urban design perspective. Highlights: Agroecosystems could act as activators for a post-covid development model the urban design project has the opportunity to integrate different sectoral tools, achieving concrete sustainable and regenerating goals the research-by-design approach can give an innovate view to understand and intervene in coevolutionary processes through mechanisms of composition and decomposition